chemical characterization and evaluation of biological activity of zizyphus lotus extractable compounds and new bioactive semisynthetic derivatives of alizarin from rubia tinctorum - ZAZOULI SOFIA (Faculté des Sciences et des Techniques, Béni Mellal - Doctorat ou Doctorat National, 2020)
Zizyphus lotus L. (Z. lotus) has been used by humans since ancient times, either as food or in traditional medicine. This shrub species is recognized to exhibit several biological activities, such as antitumor, antiangiogenic, anti-inflammatory, antidiabetic, anti-ulcerogenic, anti-spasmodic, antioxidant, and analgesic proprieties. However, little is known about their chemical composition. Thus, a detailed chemical characterization of extractable components, namely triterpenic acids and phenolic compounds, may valorize the Z. lotus plantation, due to their antioxidant, antitumor, and antimicrobial activities. Within this work, we studied the trimethylsilylation dichloromethane extract of different morphological parts of Z. lotus (seeds, pulp, leaves, and root barks) by GC-MS. We detected and quantified 123 compounds, from which fatty acids and triterpenic acid are the major families of lipophilic components present in Z. lotus, followed by sterols, long-chain aliphatic alcohols and aldehydes, monoglycerides, and aromatic compounds and other compounds. In this study was also identified and quantified the phenolic compounds for the first time of methanol/water/acetic acid (49.5:49.5:1) of the different morphological parts of Z. lotus by HPLC-UV-MSn . Seventy-eight phenolic compounds were identified as constituents of Z. lotus that belonged to phenolic acids, proanthocyanidins, flavonoid glycosides, acylated flavonoid and derivatives. Phenolic-rich extracts of roots bark and leaves were revealed the highest antioxidant potential. On the other hand for the antibacterial activity, the phenolic-rich extract of root barks showed the highest potential, especially against MRSA strain. While leaf lipophilic extract exhibited the highest activity against the E. coli growth. Pulp lipophilic and phenolicrich extracts did not prevent the strains grown in the concentration tested, while lipophilic seeds and leaf extract were highly active against S. epidermidis. Z. lotus lipophilic extract of root barks demonstrated higher inhibitory effects against human tumor cell line of MDA-MB231, MCF-7, and HepG2. The exposing MDA-MB-231 cell for 48 h, to the respective IC50 concentration of root barks lipophilic extract, showed its ability to stop cell migration, arresting cell cycle at G2, and processes apoptosis as well as the downregulation of the PI3K/Akt pathway. Z. lotus has the potential to be exploited as a source of bioactive compounds that can be applied in the formulations of different ingredients for the food and pharmaceutical industry. Chemical modifications in the side chain are one common approach in drug discovery for improving the therapeutic potential of some compounds. Our main interest in the second part was to modify the basic skeleton of anthraquinone by incorporating a pyridine moiety or dioxepine ring on its hydroxyl group. Rubia tinctorum (R. tinctorum) is another Mediterranean species known for its anti-microbial, anti-fungal, hypotensive, analgesic, antimalarial, antioxidant, antileukemic, and mutagenic proprieties. Several anthraquinones (e.g. alizarin) have been isolated from this plant and found to be responsible for their biological activities. Therefore, an adequate quantity of alizarin was purified from the roots of R. tinctorum to be used as a platform to synthesis new bioactive derivatives. Four alizarin derivatives were synthesized. Novel compounds were characterized using spectroscopic analysis, i.e. 1D (1H and 13C) nuclear magnetic resonance (NMR), electrospray ionization-mass spectrometry (ESI-MS) studies, and Fourier transform infrared (FT-IR) tools. Through computational study based on density functional theory (DFT/B3LYP) using basis set 6-311G+ (d, p) a number of chemical Quantum descriptors and MEP map were computed to predict the reactivity and the reactive sites on the ligands. In addition, the physical and chemical structure-property was found by single-crystal X-ray diffraction data. The Hirshfeld surface analysis was also computed to investigate the intermolecular interactions in the solid-state.
Keywords: 1. Natural Sciences; 1.3 Physical sciences